Helicity and Spin of Linearly Polarized Hermite-Gaussian Modes - M. Fernandez-Guasti; J. Hernández (Advances in Mathematical Physics)
The angular momentum content and propagation of linearly polarized Hermite-Gaussian modes are analyzed. The helicity gauge invariant continuity equation reveals that the helicity and flow in the direction of propagation are zero. However, the helicity flow exhibits nonvanishing transverse components. These components have been recently described as photonic wheels. These intrinsic angular momentum terms, depending on the criterion, can be associated with spin or orbital momentum. The electric and magnetic contributions to the optical helicity will be shown to cancel out for Hermite-Gaussian modes. The helicity ϱAC here derived is consistent with the interpretation that it represents the projection of the angular momentum onto the direction of motion.